Engineering geological properties of oil-contaminated granitic and metasedimentary soils - Zulfahmi Ali Rahman,; Umar Hamzah,; Noorulakma Ahmad, (Universiti Kebangsaan Malaysia, 2011)
Hydrocarbon is a light-non aqueous phase liquid or known as LNAPL. It poses environmental hazard if accidentally spilled out into the soil and water systems as a result of its insoluble nature in water. LNAPL component infiltrates into soil through pore spaces and afloat at the top of groundwater level. Some of this hydrocarbon would trap and clog within the voids, difficult to remove and costly to clean. The occurence of hydrocarbon in the soil definitely degraded the behaviour of soils in terms of engineering properties. This study aimed to investigate the engineering properties of oil-contaminated soil for two different residual soils originally developed from in-situ weathering of granitic and metasedimentary rocks. The physical characterisations of the soil were determined including particle size distribution, specific gravity test and x-ray diffraction (XRD). The engineering parameters for the contaminated and uncontaminated soils were Atterberg limits, compaction and soil shear strength (UU tests). The amounts of hydrocarbon added to soil were varied at 0%, 4%, 8%, 12% and 16% of dried weigth of soil samples. The results from the particle size distribution analysis showed that residual soil from granitic rock comprises of 38% sand, 33% silt and 4% clay while metasedimentary soil consists of 4% sand, 43% silt dan 29% clay. The mean values of specific gravity for the granitic and metasedimentary soils were 2.56 and 2.61, respectively. The types of minerals present in granitic soil sample were quartz, kaolinite and gibbsite while metasedimentary soil consists of quartz and kaolinite. The Atterberg limits value decreased as a result of increasing amount of added hydrocarbon into the soil. A similar behaviouir was observed with the values of maximum dry density and optimum water content with increasing hydrocarbon content. The overall unconsolidated undrained shear strength, Cu showed a decreasing trend with the increase in hydrocarbon content.